L’Approche Orientée Objets ou l’EuroWordNet s’adapte mieux à la traduction automatique? Partie I: origines, principes, organisation des données - Szramek-Karcz, Sonia (Neophilologica, 2013)
Lexical databases such as AOO or EWN are built in order to enable machine translation of written word. The author’s intention is to test the applicability of the above listed databases in machine translation and to choose the one that proves to be more successful. The presentation of final results consists of two parts. Part I is the analysis of factors influencing the process of machine translation with the use of AOO and EWN that is to say: steps in database design, their theoretical aspects and the categorization of lexical items. In author’s belief, the above mentioned elements exert profound influence on the result of machine translation produced with the use of one of the herein described lexical databases. The second part of the presentation touches on the matters of hierarchy, semantic inheritance and word-sense disambiguation.